Real-time hybrid testing using the unconditionally stable explicit CR integration algorithm. - Chen, Cheng
Real-time hybrid testing combines experimental testing and numerical simulation, and provides a viable alternative for the dynamic testing of structural systems. An integration algorithm is used in real-time hybrid testing to compute the structural response based on feedback restoring forces from experimental and analytical substructures. Explicit integration algorithms are usually preferred over implicit algorithms as they do not require iteration and are therefore computationally efficient. The time step size for explicit integration algorithms, which are typically conditionally stable, can be extremely small in order to avoid numerical stability when the number of degree-of-freedom of the structure becomes large. This paper presents the implementation and application of a newly developed unconditionally stable explicit integration algorithm for real-time hybrid testing. The development of the integration algorithm is briefly reviewed. An extrapolation procedure is introduced in the implementation of the algorithm for real-time testing to ensure the continuous movement of the servo-hydraulic actuator. The stability of the implemented integration algorithm is investigated using control theory. Real-time hybrid test results of single-degree-of-freedom and multi-degree-of-freedom structures with a passive elastomeric damper subjected to earthquake ground motion are presented. The explicit integration algorithm is shown to enable the exceptional real-time hybrid test results to be achieved.
Keywords: Integration algorithm; Real-time hybrid testing; Stability; Explicit; Discrete transfer function